THE EXISTENCE OF VEILED WOMEN IN THE DIGITAL ERA - Fatimah Fatimah; Ahmad Ridwan; Anggaunita Kiranantika; Mohammad Taufik Murtadho (UNIVERSITAS SEBELAS MARET (UNS), 2025)
This research explores the experiences of veiled women in the digital era, particularly in Surabaya. Using Alfred Schutz's phenomenological approach, this research examines how veiled women express their identity and respond to social stigma through social media. Digital platforms become an important space for them to share their beliefs, build communities, and redefine how society perceives them. However, these platforms also bring challenges in the form of negative stereotypes and discrimination, both directly and indirectly. The research data was obtained through in-depth interviews with veiled women who actively use social media. The results showed that social media became an important space for veiled women to build positive narratives, expand social networks, and counter negative stereotypes. However, they also face challenges in the form of online discrimination, negative comments, and social pressure. Each subject shows different strategies: some utilize social media for da'wah, some are cautious in sharing content, and some are more selective in showing their veiled identity. The findings emphasized the role of social media as a dynamic space for negotiating social identity, as well as the importance of lifeworld, intersubjectivity, and typification in this process. The novelty of this research lies in exploring the experiences of veiled women in digital spaces, which extends previous studies that focus more on physical social interactions. The results of this study are expected to enrich the literature on gender, religion, and technology, as well as provide practical insights for religious moderation efforts and empowerment of veiled women's groups in the digital era.